The effects of Co2+ and Zn2+ on the contents of protein, abscisic acid, proline and chlorophyll in bean (Phaseolus vulgaris cv. Strike) seedlings - Zengin, Fikriye Kirbag (Triveni Enterprises, 2006)
17-day-old bean plants (Phaseolus vulgaris cv. Strike) were used to analyze the effects of Co2+ and Zn2+ on the time course of proline, total protein, chlorophyll and abscisic acid (ABA) levels in leaves. Controls, Co2+ and Zn2+-treated plants were grown for 8 days in Hoagland solution. Samples were taken at 2 day intervals. Proline, chlorophyll (a+b) and total protein contents of 17 day old primary leaves were determined by a spectrophotometer. ABA contents in roots and leaves of the seedlings were measured by high-pressure liquid chromatography. The presence of Zn2+ and Co2+ significantly increased the ABA contents in roots and leaves (p<0.05 or p<0.01). The increase of the abscisic acid content in the leaves was related to the content of the roots. This was further substantiated by enhanced accumulation of proline in the leaves of seedlings exposed to zinc and cobalt. The contents of chlorophyll (a+b) and total protein decreased with the concentration of both metals (p<0.05 or p<0.01). Cobalt proved to be comparatively more toxic than zinc. © Triveni Enterprises.
Keywords: Abscisic acid; Chlorophyll; Heavy metal; Proline; Protein